Developing a Coherent System for the Assessment of Writing Abilities: Tasks and Tools - Muñoz, Ana Patricia; Mueller, Jonathan; Álvarez, Martha E.; Gaviria, Sandra (Íkala, Revista de Lenguaje y Cultura, 2006)
This article discusses the design and validation of a writing assessment system. Two main processes are addressed: validation of the construct and the writing test prompts, and design and validation of scoring instruments. Construct validation included defining and aligning the construct, the standards, and the nature of the assessment tasks. The validation of tasks was determined by analyzing task content against a set of criteria to design appropriate writing tasks and by surveying students' understanding of the prompts. Finally, scoring rubrics were designed based on the standards and the construct. To validate the rubrics, their alignment with the construct and the standards was established, as well as the estimation of their inter-rater reliability (r = > 0,7). Received: 09-03-06 / Accepted: 19-07-06 How to reference this article: Muñoz, A. P.; Mueller, J.; Álvarez, M. E. & Gaviria, S. (2006). Developing a Coherent System for the Assessment of Writing Abilities: Tasks and Tools. Íkala. 11(1), pp. 265 – 307